Anti-diabetic effect of aqueous fruit extract of Borassus aethiopum (Mart.) in alloxan-induced diabetic rats - Christopher Larbie,; Jeremiah Issaka,; Marina Tandoh, (International Journal of Phytomedicine, 2016)
Introduction: Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both. The chronic hyperglycemia is associated with long-term damage, dysfunction, and failure of various organs, especially the eyes, kidneys, nerves, heart, and blood vessels and is among the top ten causes of death in the world. Borassus aethiopum Mart. (family Arecaceae) is a plant species of Borassus palm found widely across Africa. It serves an important source of food, providing edible fruits, and nuts, and also has a number of pharmacological uses that have been reported in some parts of the world. Objective: The current study was aimed at assessing the phytochemical constituents as well as the antidiabetic and hypolipidaemic effect of fruit extract of B. aethiopum in alloxan-induced diabetic rats. Materials and Methods: The fruits extract was prepared (FEB) and phytochemical constituents evaluated using standard methods. The antidiabetic and hypolipidaemic properties in alloxanized rats assessed for 7 and 28 days. Normoglycaemic and alloxan-induced diabetic rats were treated with FEB at doses of 100 mg, 250 mg and 500 mg/kg body weight. Observations on body weight, relative organ weight, haematological and biochemical parameters were measured in both acute and sub-chronic circumstances. Results: The presence of tannins, saponins, glycosides, triterpenoids and alkaloids were detected. Fasting blood glucose was reduced significantly (p<0.05) in diabetic rats in acute study at a dose of 500 mg/kg body weight and at 250 mg and 500 mg/kg body weight in sub-chronic studies. WBC and PLT levels were significantly increased after treatment with 500 mg/kg body weight. Urea and ALT levels also reduced significantly in both acute and sub-chronic studies. Conclusion: The aqueous fruit extract of B. aethiopum is antidiabetic. It was also found to be nephron- and hepato-protective as well as boosting the immunity of the animals.